ANALISIS IMPLEMENTASI PENGUATAN KARAKTER PROFIL PELAJAR PANCASILA PADA SISWA KELAS IV DI SD - Sarina Murni; Dr Sarah Fazila,S.Si,M.Pd; Rahma Hayati Siregar,M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Strengthening the character of Pancasila student profiles in grade IV students is still considered less than optimal. The purpose of this study is (1) to find out and describe the Analysis of the implementation of strengthening the character of Pancasila student profiles in grade IV students at SDN 6 Muara Dua. (2) to find out and describe the obstacles during the implementation of strengthening the character of Pancasila student profiles in grade IV students at SDN 6 Muara Dua. (3) to find out and describe the solutions during the implementation of strengthening the character of Pancasila student profiles in grade IV students at SDN 6 Muara Dua. This study uses a qualitative approach with a descriptive research type. The results of the study show that (1) grade IV students at SDN 6 Muara Dua have not fully integrated the maximum character according to the dimensions of the Pancasila Student Profile, out of 20 students only 70% can be said to show maximum character, the rest are still categorized as not yet. (2) the main obstacles faced by a teacher in integrating the Pancasila student profile in grade IV students at SDN 6 Muara Dua are time constraints and different student backgrounds. (3) solutions in integrating the character of Pancasila student profiles by recognizing student backgrounds and changing the approach. Thus, it can be concluded that the implementation of strengthening the character of Pancasila student profiles in grade IV students is still categorized as not fully integrating the maximum character.